1992
DOI: 10.1128/mcb.12.1.155
|View full text |Cite
|
Sign up to set email alerts
|

Identification of replication factor C from Saccharomyces cerevisiae: a component of the leading-strand DNA replication complex.

Abstract: A number of proteins have been isolated from human cells on the basis of their ability to support DNA replication in vitro of the simian virus 40 (SV40) origin of DNA replication. One such protein, replication factor C (RFC), functions with the proliferating cell nuclear antigen (PCNA), replication protein A (RPA), and DNA polymerase 8 to synthesize the leading strand at a replication fork. To determine whether these proteins perform similar roles during replication of DNA from origins in cellular chromosomes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
142
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(147 citation statements)
references
References 54 publications
5
142
0
Order By: Relevance
“…M13mp2opl4 DNA was propagated in E. coli JM109 cells as described by Sanderson and Mosbaugh [30], and single-stranded M13mp2op14 DNA was purified from the culture supernatant using the CTAB DNA precipitation method [31,32]. The single-stranded M13 DNA circles were annealed to a complementary 5′-phosphorylated oligonucleotide (5′-CCCAGTCACGTCATTGTAAAACG-3′) in reactions (6 μ1 × 50 μ1) containing 20 mM Tris-HCl pH 7.4, 2 mM MgCl 2 , 50 mM NaCl, 0.4 μM ssM13, and 1.2 μM 5′-end phosphorylated oligonucleotide.…”
Section: Preparation Of Dna Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“…M13mp2opl4 DNA was propagated in E. coli JM109 cells as described by Sanderson and Mosbaugh [30], and single-stranded M13mp2op14 DNA was purified from the culture supernatant using the CTAB DNA precipitation method [31,32]. The single-stranded M13 DNA circles were annealed to a complementary 5′-phosphorylated oligonucleotide (5′-CCCAGTCACGTCATTGTAAAACG-3′) in reactions (6 μ1 × 50 μ1) containing 20 mM Tris-HCl pH 7.4, 2 mM MgCl 2 , 50 mM NaCl, 0.4 μM ssM13, and 1.2 μM 5′-end phosphorylated oligonucleotide.…”
Section: Preparation Of Dna Substratesmentioning
confidence: 99%
“…PCNA LC59 was overproduced in E. coli BL21 (DE3) and purified as described previously for wild-type PCNA, except that the LC59 double mutant flowed through, rather than binding to, the phenyl-Sepharose column [32].…”
Section: Protein Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Human PCNA was purified from bacterial lysate by QSepharose, S-300 Sephacryl gel filtration, and Phenyl-Superose chromatography (19). Protein concentrations were determined by a Bradford-based assay (Bio-Rad) and verified by Coomassie Blue staining of SDS-PAGE gels.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, it has been shown that two additional polypeptides are copurified with the activity of DNA polymerase III (Hashimoto et al 1998). Together with DNA polymerase II or III, three accessory protein complexes, RF-A (RP-A), RF-C, and PCNA, are required for a highly processive DNA synthesis in vitro (Burgers 1991;Yoder & Burgers 1991;Fien & Stillman 1992).…”
Section: Introductionmentioning
confidence: 99%